Matching Regular Expressions on uncertain data - Gil, José Arturo; Santini, Simone (Algorithmica, 2022)
In this paper we study regular expression matching in cases in which the identity of the symbols received is subject to uncertainty. We develop a model of symbol emission and uses a modification of the shortest path algorithm to find optimal matches on the Cartesian Graph of an expression provided that the input is a finite list. In the case of infinite streams, we show that the problem is in general undecidable but, if each symbols is received with probability 0 infinitely often, then with probability 1 the problem is decidable.